Case report: Persistent hypogammaglobulinemia in thymoma-associated myasthenia gravis: the impact of rituximab or Good's syndrome? - Ren, Jingru; Wang, Jianchun; Liu, Ran; Guo, Jing; Yao, Yan; Luo, Jingjing; Hao, Hongjun; Gao, Feng (Frontiers in Neurology, 2023)
Introduction Rituximab (RTX) showed good efficacy and safety for patients with myasthenia gravis. However, the percentage of peripheral CD20+ B cell may be absent for years after low dose of RTX treatment. Persistent hypogammaglobulinemia and opportunistic infection may occur in patients under treatment of RTX with thymoma relapse. Case representation We report a case of refractory myasthenia gravis. After two doses of 100 mg rituximab, the patient developed transient neutropenia. The peripheral blood CD20+ B cell percentage was 0 more than 3 years. Eighteen months later, the patient's symptoms relapsed with thymoma recurred. She had persistent hypogammaglobulinemia and multiple opportunistic infections. Conclusion In MG patient under B cell depletion therapy had thymoma relapse, Good's syndrome may induce prolonged B cell depletion, hypogammaglobulinemia and opportunistic infections.